PHOTOCHEMICAL INVESTIGATION OF VINBLASTINE IN 43 CULTIVARS OF CATHARANTHUS ROSEUS L. - S.E AJADI; R VERPOORTE (Journal of Research in Medical Sciences, 2000)
Background. Vinblastine is one of the alkaloids extracted from Catharanthus roseus L. which is used for the treatment of Hodgkin's disease, lymphoma, and leukemia in children. In spite of the progresses in the synthesis of many drugs, synthesis of vinblastine is not feasible and it has been extracted from plant so far. In this study we used a screening method to facilitate selection for the best cultivar with a higher yield.
Methods. The leaves of the 43 cultivars of C. roseus L was freeze dried and vinblastine was extracted with trifluroacetic acid 0.06% in water. The extraction was analysed by HPLC, using a gradient solvent system.
Results and Discussion. The results of this study indicates that the amount of vinblastine is variable in different cultivars. The concentration of vinblastine in cultivar NO. 41 [C. roseus L (G. DON)] is 5.1 times mare than the means of vinblastine in all cultivars. The cultivar No. 23 [C. roseus L (Pacifica Punch)] has the minimum concentration of this alkaloid.